1985
DOI: 10.1103/physrevlett.54.414
|View full text |Cite
|
Sign up to set email alerts
|

Collision-Strength Shift in Electron-Impact Single and Double Ionization of Sb and Bi Ions

Abstract: At energies greater than 200 eV the electron-impact single-ionization cross sections for Sb 2 + (4d l0 5s 2 5p) and Bi 2+ (5d l0 6s 2 6p) ions, o-2 ,3, are larger than the corresponding cross sections, 0x2, for Sb 1 + and Bi 1 + ions, respectively. This extraordinary behavior is a consequence of the fact that the 4d(5d) hole configurations goes from autoionization to bound when the charge state of the Sb (Bi) ions is increased from +1 to + 2. Additionally, multiple ionization measurements (0-1,3 for Sb and ox3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…12.25 eV [11]). We have previously observed [13] a similar extraordinary behavior for the corresponding cross sections 01,2 and 02,3 for Sb and Bi ions, where the Ad (5d) hole configuration goes from autoionizing to bound when the charge state is increased as one goes from Sb* (Bi + ) to Sb 2+ (Bi 2+ ). The effect in the fullerene ions may be similarly caused by autoionizing versus bound hole configurations.…”
Section: Ionization and Fragmentation Of Fullerene Ions By Electron Isupporting
confidence: 68%
“…12.25 eV [11]). We have previously observed [13] a similar extraordinary behavior for the corresponding cross sections 01,2 and 02,3 for Sb and Bi ions, where the Ad (5d) hole configuration goes from autoionizing to bound when the charge state is increased as one goes from Sb* (Bi + ) to Sb 2+ (Bi 2+ ). The effect in the fullerene ions may be similarly caused by autoionizing versus bound hole configurations.…”
Section: Ionization and Fragmentation Of Fullerene Ions By Electron Isupporting
confidence: 68%
“…Loch et al [13] studied electron impact ionization of Bi q+ , q = 1-10 and compared configurationaverage distorted wave calculations to experimental results finding good agreement between both for all ion stages. Müller et al [14] employed crossed electron and ion beams to study single and double ionization of Bi I where they observed a crossing of the cross-sections for singly and doubly-charged Bi ions at electron energies over 200 eV.…”
Section: Introductionmentioning
confidence: 99%